Potensi Peningkatan Kesejahteraan Petani Kopi Musim Kecamatan Sitinjo Kabupaten Dairi Melalui Budidaya Kopi - Muhammad Luthfi Ihsanuddin (Marpokat: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of writing this article is to find out the welfare conditions of farmers, and the potential for farmers' welfare through coffee cultivation in Sitinjo District, Dairi Regency. The method used in this study is a case study that describes the facts that occurred at the research site, for this reason, the writer does writing using several kinds of preparation, 1) Observation (observation), interview (interview), and Documentation, namely data collection. The results of this study are: Coffee cultivation has not fully proceeded as it should be done so the welfare of coffee farmers in Sitinjo District is less prosperous, several factors cause the potential for coffee cultivation not to go well and the welfare of coffee farmers is not evenly distributed, namely, from the production of coffee beans, namely from a lack of maintenance of the fields or coffee plantations which is still not very good so that not all of the coffee produced is good, so the price of the coffee is also different and some are even affected by pests, not to mention the selling price of coffee beans that are not stable and marketing that is not good from in terms of price from farmers to collectors. So as to produce less yields which has a negative impact on reducing farmers' income and affecting their less improved socio-economic conditions. Keywords: Potential; Cultivation; Welfare.